Aplicabilidade de reações de Fenton e foto-Fenton no tratamento de glifosato comercial - Souza, Danilo Rodrigues de (2011)
In this study, the thermal and photochemical Fenton reactions were adopted for the photodegradation of commercial glyphosate. Furthermore, it was proposed the simultaneous addition of Fe2+/Fe3+ and potassium oxalate to empower them. In bench scale, employing 4 L of a solution containing glyphosate, the evaluated parameters were the degradation efficiency by comparing reactions based only in Fe2+ and reactions using simultaneously Fe2+ and Fe3+, Fe2+ and Fe3+ concentration influence, potassium oxalate influence and its concentration effect, hydrogen peroxide influence and its concentration effect. The results showed that the simultaneous use of Fe2+ and Fe3+ and potassium oxalate was more effective in reducing the organic load, with the formation of dissolved inorganic phosphate showing the glyphosate degradation. Total organic carbon was reduced by 74 % and nearly 90 % of added hydrogen peroxide was consumed. In the presence of oxalate, nearly39 mgL-1 inorganic phosphate was produced in the photocatalytic effluent, whereas in reactions without oxalate only 21 mgL-1 were produced. Moreover, it can also be shown that the excess of Fe2+, Fe3+, oxalate and hydrogen peroxide affect the photocatalytic assays. In a batch system, working with 50 L of the model-effluent, using a compound parabolic collector (CPC) reactor to promote photolysis with sunlight, 62% of organic matter was mineralized with a consumption of 100% of the added hydrogen peroxide. For these experiments the amount of inorganic phosphate reached 41 mgL-1 in the effluent after photocatalysis. The results obtained by liquid chromatography proved the feasibility of using the combination of Fe2+/Fe3+/oxalate. The specific mineralization of glyphosate reached 100% in just 60 min of photocatalysis. The toxicity of the photocatalysed samples were evaluated by germination assays using lettuce seeds. Results showed that, in comparison to the control samples, the average germination after 120 min of photocatalysed glyphosate reached 100% while the rate of stem growth reached 74%. The reduction of toxicity was confirmed as lettuce seeds exposed to commercial glyphosate with no photocatalytic treatment, showed no germination.